To Study the Bianchi type V Cosmological Model with Quadratic Equation of State in Modified theory of Gravity. Issue 1 (1st May 2022) - Kumar, R; Tandon, R; Gupta, J
Abstract: In this paper, Bianchi type-V cosmological model in perfect fluid with quadratic equation of state p= αρ 2 -ρ, where α≠ 0, has been studied in modified theory of gravity. The general solution of the f ( R, T ) equations for Bianchi type-V space-time has been obtained by considering a law of variation of scale factor which yields a time dependent deceleration parameter. The model represents the transition of the universe from early deceleration phase to the recent accelerated expansion phase.